Profitability, Company Size, Financial Leverage, and Dividend Payout Ratio Influencing Income Smoothing Practices - Anita Wulan Natasari Sukarno Putri; Novrida Qudsi Lutfillah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study examines and analyzes the effect of profitability, company size, financial leverage, and dividend payout ratio on income smoothing practices. The population used in this study are mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. This study uses secondary data with a sample of 10 companies selected by purposive sampling method. Data analysis was performed using statistics with SPSS 21 tools. Based on the data analysis results using the t-test, it was known that partially profitability, company size, financial leverage, and dividend payout ratio did not significantly affect income smoothing practices. Based on the results of data analysis using the F test, it is known that simultaneously profitability, company size, financial leverage, and dividend payout ratio do not have a significant effect on income smoothing practices.